The balanced scorecard: Fashion or virus? - Dag Øivind Madsen; Kåre Slåtten (Administrative Sciences, 2015)
The Balanced Scorecard (BSC) is a one of the most popular and contagious management ideas of our time. In previous research the diffusion and institutionalization of the BSC has been viewed through different theoretical lenses, most notably the management fashion perspective. Recently the virus perspective has been introduced as an alternative theory of how management ideas spread, but so far no study has applied this theory in the context of the BSC. In this paper we show that the fashion and virus perspectives provide complementary insights into the diffusion and institutionalization of the BSC. The fashion perspective is particularly well suited for explaining the infectiousness of the BSC and the ways in which organizations are exposed to the BSC idea. The virus theory can better explain how the BSC idea is implemented as a practice in organizations, and the different trajectories that the BSC idea may take in different contexts. A combination of these two perspectives provides a fuller picture of the diffusion and institutionalization of the BSC.
Keywords: 350; Balanced Scorecard; management idea; virus; fashion; diffusion; institutionalization